Depression in youths with early life adversity: a systematic review and meta-analysis - Yu, Zengyan; Cao, Yunhua; Shang, Tinghuizi; Li, Ping (Frontiers in Psychiatry, 2024)
Background: Globally, early-life adversity (ELA) is linked to an increased risk of developing depression in adulthood; however, only a few studies have examined the specific effects of various types of ELA on depression in children and adolescents. This meta-analysis explores the association between the subtypes of ELA and the risk for youth-onset depression. Methods: We searched three electronic databases for reporting types of ELA, namely, emotional abuse, physical abuse, sexual abuse, emotional neglect, physical neglect, family conflict/violence, divorce, low socioeconomic status, and left-behind experience, associated with depression before the age of 18 years. Our meta-analysis utilized the odds ratio (OR) and relied on a random effects model. Large heterogeneous effects were detected. Some factors moderated the association between ELA and depression in youths. The homogeneity of variance test and meta-regression analysis were used to detect these relationships. Results: A total of 87 studies with 213,006 participants were ultimately identified via several strategies in this meta-analysis. Individuals who experienced ELA were more likely to develop depression before the age of 18 years old than those without a history of ELA (OR=2.14; 95% CI [1.93, 2.37]). The results of the subgroup analysis revealed a strong association between ELA and depression in youth, both in terms of specific types and dimensions. Specifically, emotional abuse (OR = 4.25, 95% CI [3.04, 5.94]) was more strongly related to depression in children and adolescents than other forms of ELA were. For both dimensions, threat (OR = 2.60, 95% CI [2.23, 3.02]) was more closely related to depression than deprivation was (OR = 1.76, 95% CI [1.55, 1.99]). Conclusion: This meta-analysis revealed that the adverse effects of a broader consideration of ELA on the risk of youth-onset depression vary according to the subtypes of ELA. Keywords: Depression; Adversity; Threat; Deprivation; Youth